Arc volcano of Japan generation of continental crust from the mantle - Yanagi, Takeru (Lecture notes in earth sciences, 2011)
This book presents an analysis of our current knowledge on the origin of the Earth?s continental crust. There are two aspects to consider: tectonic and igneous processes. Tectonic aspects include sedimentary accretion, terrane accretion, and continental collision at continental margins, in association with plate subduction. These processes result in the formation of large mountain belts, the building up of which literally grows the continents. However, these tectonic aspects are concerned with material recycling within the crust, and hence do not contribute to volumetric growth of continental crust. Igneous processes concern separation of continental crust from the mantle and result in the volumetric growth of continental crust. Therefore, the main focus of this book is to systematically examine why and how the Earth?s continental crust forms, by evaluating magmatic processes at island arcs where new continental crust